2019
DOI: 10.31234/osf.io/ukm3b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does the understanding of complex dynamic events at 10 months predict vocabulary development?

Abstract: By the end of their first year, infants are able to interpret many different types of complex dynamic visual events, such as caused-motion, chasing, and goal-directed action. The present work examined whether there are meaningful individual differences in infants' ability to represent dynamic causal events in visual scenes and whether these differences influence vocabulary development. As part of the longitudinal Language 0-5 Project, 78 10-month-old infants were tested on their ability to interpret three dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This is increasingly becoming a concern in language acquisition research (Kidd et al, 2018a ; Donnelly and Kidd, 2020 ). For example, in a recent study aimed at examining whether the comprehension of dynamic motion events by 10-month-old children was related to their vocabulary development, Durrant et al ( 2020 ) found that looking times did not reliably capture individual differences. They point out that little is known about the drivers of the attention of children on these sorts of tasks; it may be that the comprehension of children is non-linearly related to looking time.…”
Section: Discussionmentioning
confidence: 99%
“…This is increasingly becoming a concern in language acquisition research (Kidd et al, 2018a ; Donnelly and Kidd, 2020 ). For example, in a recent study aimed at examining whether the comprehension of dynamic motion events by 10-month-old children was related to their vocabulary development, Durrant et al ( 2020 ) found that looking times did not reliably capture individual differences. They point out that little is known about the drivers of the attention of children on these sorts of tasks; it may be that the comprehension of children is non-linearly related to looking time.…”
Section: Discussionmentioning
confidence: 99%